2009
DOI: 10.1111/j.1365-2109.2009.02308.x
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of macroalgae meal (Macrocystis pyrifera) as feed ingredient for rainbow trout (Oncorhynchus mykiss): effect on flesh fatty acid composition

Abstract: Inclusion of macroalgae meal (Macrocystis pyrifera) as feed ingredient for rainbow trout (Oncorhynchus mykiss): Effect on flesh fatty acid composition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 18 publications
3
36
0
Order By: Relevance
“…However, it seems that the effect of algae meal on fish carcass composition is related to their nutritional value and dietary inclusion level. The other influencing factors are fish species, size, age and experimental protocol (Diler et al, 2007;Ergün et al, 2008;Dantagnan et al, 2009;Güroy et al, 2007). Phagocytes including neutrophils and macrophages are considered as important cellular components of non-specific immune response and play an important role in the host defense against invading pathogens by producing reactive oxygen (a) (b) intermediates known as respiratory burst activity (Whyte, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that the effect of algae meal on fish carcass composition is related to their nutritional value and dietary inclusion level. The other influencing factors are fish species, size, age and experimental protocol (Diler et al, 2007;Ergün et al, 2008;Dantagnan et al, 2009;Güroy et al, 2007). Phagocytes including neutrophils and macrophages are considered as important cellular components of non-specific immune response and play an important role in the host defense against invading pathogens by producing reactive oxygen (a) (b) intermediates known as respiratory burst activity (Whyte, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have declared that a low level dietary inclusion of Ulva meal (3-5 %) enhanced growth, feed utilization, immune response, and lipid mobilization in numerous finfish species such as gilthead seabream (Wassef et al, 2005), tilapia (Ergün et al, 2009), rainbow trout , mugil Mugil cephalus (Wassef et al, 2001), black sea bream Acanthopagrus schlegeli (Nakagawa et al, 1993) and snakehead Channa striatus (Hassan and Hashim, 1995). Other studies have shown that a 5% or 10% inclusion of dietary Ulva meal had no negative effects on the growth performance of juvenile European seabass Dicentrarchus labrax (Valente et al, 2006), tilapia , and rainbow trout, Oncorhynchus mykiss of different sizes (Güroy et al, 2013;Dantagnan et al, 2009;SolerVila et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Dantagnan et al (2009) have reported that the inclusion of <3% Macrocystis pyrifera meal in diets for rainbow trout did not have a negative impact on growth and feed parameters and improved the quality of meat. In studies with green algae Ulva rigida; Ergün et al (2009) have reported that 5% inclusion of Ulva meal at both dietary lipid levels improved the growth performance, feed efficiency, and body composition of Nile tilapia (Oreochromis niloticus).…”
Section: Discussionmentioning
confidence: 99%
“…Hernandez, Borguez & Mansilla, 2009;Soler-Vila, Coughlan, Guriy & Kraan, 2009;Wassef, El-Sayed & Sakr, 2013). However, even when these vegetable raw materials substitutes can support growth, they can cause significant changes in the nutritional quality of the fish produced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation